Promoting a Nation with Cultural Tourism - Ghimire, Ram Prasad (Butwal Campus Journal, 2024)
This paper connects the issue of promoting a nation with cultural tourism and shows that a nation’s promotion is possible only through cultivating a humanitarian behavior, not just through the commercialization of cultural heritage. Cultural tourism incorporates both a nation’s economy as well as its typical mode of humanity that deals with the visitors from other countries in a cultured way and it inspires them to come to the nation time and again to realize themselves as true human beings, narrowing the gap between themselves and other human beings across the world.